2018
DOI: 10.1017/s1352465818000073
|View full text |Cite
|
Sign up to set email alerts
|

Are Schemas Passed on? A Study on the Association Between Early Maladaptive Schemas in Parents and Their Offspring and the Putative Translating Mechanisms

Abstract: This study provides preliminary evidence for the notion that EMSs are passed on from one generation to the next via parental coping and parenting. Our findings thus support the assumption of schema theory that EMSs are connected to the family environment in terms of adverse parenting. If further confirmed, this has relevant implications for family-based interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 33 publications
2
16
0
1
Order By: Relevance
“…Each YCI item is rated on a 6-point Likert scale from 1 ('completely untrue of me') to 6 ('describes me perfectly'). The YCI has satisfactory validity and reliability (LuKaraosmanoglu et al, 2013;Sundag et al, 2018). The internal consistency of YCI in the current study was .88.…”
Section: Young Compensation Inventory (Yci)supporting
confidence: 49%
“…Each YCI item is rated on a 6-point Likert scale from 1 ('completely untrue of me') to 6 ('describes me perfectly'). The YCI has satisfactory validity and reliability (LuKaraosmanoglu et al, 2013;Sundag et al, 2018). The internal consistency of YCI in the current study was .88.…”
Section: Young Compensation Inventory (Yci)supporting
confidence: 49%
“…The schema therapy puts more emphasis on the relation therapy, emotional experience, and discussion of early life experiences, which is based on the early maladaptive schemas [19]. Young believed that the schema is superior to other short-term therapies for the treatment of severe and chronic psychiatric disorders, such as personality disorders, depression, and chronic anxiety, drug abuse, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a few studies have investigated through which mechanisms parents' EMSs lead to their children's EMSs. Sundag et al (2018) analysed the data from 60 dyads of parents and their adult children and concluded that there were significant associations between EMSs of parents and their adult children, which are also mediated through overcompensation coping style of parents and perceived adverse parenting of their adult children. In another study, Gibson and Francis (2019) examined the mediator role of parenting style on the intergenerational transfer of EMSs using 39 mother–adult daughter dyads.…”
Section: Associations Between Early Maladaptive Schema Domains Of Parents and Their Adult Children: The Role Of Defence Stylesmentioning
confidence: 99%